Distribution of Rubber Leaf Fall Disease in the Swamp Lands of Barito Kuala District (Fountain Journal of Natural and Applied Sciences, 2024)
Swamp land is a rubber development area in South Kalimantan and rubber plants are a leading commodity in South Kalimantan, second after palm oil plants. Starting in 2019, the rubber industry in Indonesia experienced an outbreak of leaf fall disease. This disease causes a decrease in latex production of up to 50%, even in advanced conditions, infected plants will rot and die without treatment. This research aims to study the distribution of rubber leaf fall disease in the swamplands of Barito Kuala district. A  disease incidence and severity survey was carried out using a stratified random sampling method. It was observed that eight sub-districts in Barito Kuala district and Banjar district had swamp land that planted rubber. At four locations/villages in each sub-district, sample plants were taken, and it was determined that there were 25 plants diagonally. Disease incidence and severity parameters followed the International Rubber Research Development Board. The research revealed that rubber leaf fall disease has spread in four rubber-plantation sub-districts. All sub-districts surveyed were 100% affected by rubber leaf fall disease. The rubber leaf fall disease attack in the studied is quite severe with an average disease severity of 67%.Keywords: Distribution, Leaf fall disease, Rubber, Swamp land
Keywords: Rubber, Leaffall disease, Swamp land